2020
DOI: 10.1096/fj.202001768rr
|View full text |Cite
|
Sign up to set email alerts
|

Defined serum‐free three‐dimensional culture of umbilical cord‐derived mesenchymal stem cells yields exosomes that promote fibroblast proliferation and migration in vitro

Abstract: Stem cell‐derived exosomes are emerging as novel and clinically relevant cell‐free therapeutics for regenerative therapy. This work focused on investigating the stimulation of fibroblasts by exosomes derived from umbilical cord‐derived mesenchymal stem cells (ucMSC) in a defined serum‐free three‐dimensional (3D) culture. 3D culture of ucMSC was carried out in medium supplemented with KnockOut serum replacement (KO‐medium) using the Aggrewell system. ucMSC in KO‐medium formed spheroids with maintained size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 74 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…Hence, it is instructive to maintain the stemness of MSCs and maximize the efficacy of exosomes by using three-dimensional (3D) culture. The exosomes derived from 3D culture environment (3D-Exo) have been demonstrated to contain proteins and miRNAs that are mainly enriched in energy metabolism, immune regulation, spinal cord development, and neuronal regulation. , Additionally, 3D-Exo possesses higher amounts of anti-inflammatory and antiapoptotic factors than 2D culture exosomes (2D-Exo) . Therefore, 3D-Exo may hold the advantages of higher therapeutic efficiency, which will show broad potential applications in the treatment of SCI.…”
mentioning
confidence: 99%
“…Hence, it is instructive to maintain the stemness of MSCs and maximize the efficacy of exosomes by using three-dimensional (3D) culture. The exosomes derived from 3D culture environment (3D-Exo) have been demonstrated to contain proteins and miRNAs that are mainly enriched in energy metabolism, immune regulation, spinal cord development, and neuronal regulation. , Additionally, 3D-Exo possesses higher amounts of anti-inflammatory and antiapoptotic factors than 2D culture exosomes (2D-Exo) . Therefore, 3D-Exo may hold the advantages of higher therapeutic efficiency, which will show broad potential applications in the treatment of SCI.…”
mentioning
confidence: 99%
“…Although soluble factors secreted by viable MMSCs into the culture medium offer an attractive cell-free therapeutic alternative, to our knowledge, their regenerative potential has not yet been fully investigated. Therapeutic properties of secretome/exosomes were reported to be modulated by factors related to their culture condition such as cell source, oxygen tension (normoxia vs. hypoxia), growth factor composition, and physical microenvironment [ 27 ]. Most studies produced conditioned media (CM) in monolayer culture, but several studies used different 3D cultures, in particular, cell spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…Spheroid cultures need a spatial handling but yield more cells compared to conventional monolayer cultures, and thus more secreted factors [ 28 ]. Three-dimensional cell culture enables better recapitulation of the in vivo environment and was proven to be beneficial for MMSC culture in terms of enhancing their therapeutic potential [ 27 ]. In addition, cells located at the center of the spheroid may be in a relative hypoxic condition compared to cells on the surface, which leads to increase of certain pro-regenerative paracrine signaling molecules and immunomodulatory factors [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the co-culture of MSCs with nucleus pulposus cells not only stimulated the NPCs proliferation but also attenuated cell apoptosis in the degenerated IVD. Studies have shown that exosomes derived from MSC replicate these therapeutic effects of their parent cells ( Faruqu et al, 2021 ; Zhu et al, 2021 ). For in vitro disc degeneration model induced by different biochemical challenges, including H 2 O 2 , LPS, IL-1β, TNF-ɑ, acidic pH, and high glucose, the administration of MSC-derived exosomes exerts pro-proliferation and anti-apoptosis effect via distinct mechanisms.…”
Section: Impacts Of Msc-derived Exosomes On Ivddmentioning
confidence: 99%